Beyond access: barriers to internet health information seeking among the urban poor. (20th May 2016) - McCloud, Rachel F; Okechukwu, Cassandra A; Sorensen, Glorian; Viswanath, K
Abstract : Objective Communication inequalities deepen health disparities even when internet access is achieved. The goal of this study is to understand how a range of barriers may inhibit individuals from low socioeconomic position (SEP) from engaging with online health information even when it is freely available. Materials and methods Detailed data were collected from 118 low-SEP individuals from a randomized controlled trial providing internet access. Measures triangulated the health-seeking experience through internet use tracked in real-time, call log data, and self-reported barriers. Negative binomial regression models were fitted with technology and perceived predictors, and our outcome, health information seeking, and then stratified by medical status. Results Participants experienced a median of two computer issues (median 6 days) and two internet issues (median 6.5 days). Duration of internet problems was associated with a decrease in the rate of internet health information seeking by a factor of 0.990 ( P = .03) for each additional day. Participants with a medical problem who were frustrated in their search for health information had half the rate of health information seeking of those who were not frustrated (incidence rate ratio = 0.395, P = .030). Discussion Despite IT support, participants still experienced internet connectivity issues that negatively impacted their health information seeking. Frustration in their search to find information may serve as an additional barrier to those who have medical issues. Conclusion After initial internet access, a second-level digital divide emerged due to connectivity issues, highlighting the need to understand the complex network of barriers experienced by low-SEP internet users.